2008
DOI: 10.1111/j.1745-6584.2008.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends in Chloride Concentrations in Shallow Aquifers near Chicago

Abstract: The rapid expansion of major cities throughout the world is resulting in the degradation of water quality in local aquifers. Increased use of road deicers since the middle of the 20th century in cities in the northern United States, Canada, and Europe has been linked to degraded ground water quality. In this article, Chicago, Illinois, and its outlying suburban areas are used as an example of the effects of urbanization in a historical context. A statistical study of historical water quality data was undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 22 publications
10
63
0
Order By: Relevance
“…Since baseline concentrations increased with time over the course of the study, less additional road salt runoff was needed to reach concentrations of concern in the later years of the study than in the early years, effectively changing the slope of the chloride to urban land cover relation. With baseline concentrations governed by groundwater discharges in many instances, this finding is consistent with other research that has observed elevated chloride concentrations in groundwater which has caused elevated stream concentrations (Kelly, 2008;Eyles et al, 2013).…”
Section: Temporal Trends and Relation With Land Usesupporting
confidence: 89%
See 2 more Smart Citations
“…Since baseline concentrations increased with time over the course of the study, less additional road salt runoff was needed to reach concentrations of concern in the later years of the study than in the early years, effectively changing the slope of the chloride to urban land cover relation. With baseline concentrations governed by groundwater discharges in many instances, this finding is consistent with other research that has observed elevated chloride concentrations in groundwater which has caused elevated stream concentrations (Kelly, 2008;Eyles et al, 2013).…”
Section: Temporal Trends and Relation With Land Usesupporting
confidence: 89%
“…A similar year-round influence has been noted multiple times in previous research (Williams et al, 2000;Kelly, 2008;Perera et al, 2013). This non-deicing season effect has been attributed to salt infiltrating into the shallow groundwater system thereby serving as a "reservoir" of salt that is slowly discharged into streams as baseflow.…”
Section: Seasonalitymentioning
confidence: 67%
See 1 more Smart Citation
“…Degradation of groundwater resources is a major concern in growing urban areas, as elevated chloride concentrations are indicative of anthropogenic impact (Kelly 2008), and even approach the limits of drinking water quality standards (Howard and Maier 2007). Surveys in the Greater Toronto Area documented a strong relationship between increasing chloride concentration in the groundwater and urbanization (Williams et al 1999;Howard and Maier 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio is less reliable than δ 18 O, due to more complications. On the one hand, raised levels in autochthonous groundwater are encountered in urbanized areas, because of leaky sewer systems and/or road de-icing salt (Kelly 2008). On the other hand, levels in RBF can be lower, mainly by the release of Br from organic rich muds that accumulate where river flow is reduced , and by abstraction of old RBF with a Cl/Br ratio ≤300 because it infiltrated before the salt mining industry started.…”
Section: Hydrosomesmentioning
confidence: 99%